Differences in the Proteomic and Metabolomic Response of Quercus suber and Quercus variabilis During the Early Stages of Phytophthora cinnamomi Infection - Saiz-Fernández, Iñigo; Đorđević, Biljana; Kerchev, Pavel; Černý, Martin; Jung, Thomas; Berka, Miroslav; Fu, Chuen-Hsu; Horta Jung, Marília; Brzobohatý, Břetislav (Frontiers in microbiology, 2022)
Phytophthora cinnamomi Rands is a cosmopolite pathogen of woody plants which during the last couple of centuries has spread all over the world from its center of origin in Southeast Asia. In contrast to Chinese cork oak (Quercus variabilis Blume) forests native to Asia, which are generally healthy despite the presence of the pathogen, the populations of Cork oaks (Quercus suber L.) in Europe have been severely decimated by P. cinnamomi. The present study aims at identifying the differences in the early proteomic and metabolomic response of these two tree species that lead to their differences in susceptibility to P. cinnamomi. By using micropropagated clonal plants, we tried to minimize the plant-to-plant differences in the defense response that is maximized by the high intraspecific genetic variability inherent to the Quercus genus. The evolution on the content of Phytophthora proteins in the roots during the first 36 h after inoculation suggests a slower infection process in Q. variabilis plants. These plants displayed a significant decrease in sugars in the roots, together with a downregulation of proteins related to carbon metabolism. In the leaves, the biggest changes in proteomic profiling were observed 16 h after inoculation, and included increased abundance of peroxidases, superoxide dismutases and glutathione S-transferases in Q. variabilis plants, which probably contributed to decrease its susceptibility to P. cinnamomi.
Keywords: sugars; peroxidases; phenylpropanoids; micropropagation; plant pathogen; resistance; glutathione S-transferase